Pengembangan Pariwisata Lokal Telaga Carang Sewu Melalui Pembangunan Spot Foto di Desa Laban, Kabupaten Gresik - Widyatama, Lintang Putri; cahyono, hendry (Universitas Negeri Surabaya, 2023)
Carang Sewu Lake in Laban Village, Menganti District, Gresik Regency is a potential place to be used as local tourism which has a natural landscape that is still maintained. However, it is known that the lake is still full of weeds and plastic waste, so the development of this lake aims to overcome this problem by building photo spots made of plastic waste. The development of Telaga Carang Sewu was carried out in four stages, namely, observation, licensing, making photo spot media, and program implementation. This service aims to develop Telaga Carang Sewu tourism in Laban Village more attractive without changing its original function. This local tourism development is expected to attract many tourists from inside and outside and with this it can help restore the economy of local residents.